(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2009)
The author argues that those who suffer with drug addiction live a disturbed relation to their bodies. The theoretical notion of the lived-body is explored drawing on the work of major phenomenological theorists, particularly J.H. van den Berg. The lived-body of addiction is explored by noting that the drug addict is unable to allow his body to recede, or be forgotten. Instead it is in the pleasure of drug use and the pain of drug withdrawal that the body is known. And it is an explicit knowing which leads the body to no longer function as a lived-body, but as a thing-body. This thing-body is then opened to instrumental abuse. The implications of this development are explored also with relation to interpersonal and worldly being.